2007
DOI: 10.1002/ajh.20944
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled analgesia versus continuous infusion of morphine during vaso‐occlusive crisis in sickle cell disease, a randomized controlled trial

Abstract: Intravenous morphine is the treatment of choice for severe pain during vaso‐ occlusive crisis in sickle cell disease (SCD). However, side effects of morphine may hamper effective treatment, and high plasma levels of morphine are associated with severe complications such as acute chest syndrome. Furthermore, adequate dosing remains a problem since no objective measurement of pain severity exists and analgesia should be titrated upon the patient's reported pain. Patient‐controlled analgesia (PCA) may therefore b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 35 publications
0
47
1
3
Order By: Relevance
“…This is contrary to a previous study done in a group of sickle cell disease patients in whom lower mean morphine consumption in the PCA group resulted in adequate pain relief and significantly less nausea and vomiting compared with the continuous infusion group during vaso-occlusive crises [13]. Recently this trend has changed, as consumption has been found to be equal or more compared to continuous infusion depending upon individual variability [6].…”
Section: Discussioncontrasting
confidence: 62%
“…This is contrary to a previous study done in a group of sickle cell disease patients in whom lower mean morphine consumption in the PCA group resulted in adequate pain relief and significantly less nausea and vomiting compared with the continuous infusion group during vaso-occlusive crises [13]. Recently this trend has changed, as consumption has been found to be equal or more compared to continuous infusion depending upon individual variability [6].…”
Section: Discussioncontrasting
confidence: 62%
“…[2,18] Hasta yakınlarının %35-37'sinin önerilen bolus dozu kullandığı ifade edilmektedir. [5] Çalışmamızda da kullanıcılar HKA yöntemin; ağrılı dönem süresini kısalttığını, ağrının yeniden başlama korkusunu azalttığını, ilaca ulaşa-mama korkusunu azalttığını ifade etmelerine karşın istek butonuna basmak için ağrının artmasını beklediklerini ifade etmişlerdir.…”
Section: Discussionunclassified
“…[4] Opioidlerin bu hastalarda hasta kontrollü analjezi (HKA) yöntemiyle kullanılması pek çok çalışmaya konu olmuştur. [1,5,6] Hızla analjezi sağlama-sı, saatlik doz ayarlamasının yapılabilmesi, plazmada bazal analjezik konsantrasyonu oluşturması, sağlık görevlilerinden bağımsız ilaç uygulayabilme olana-ğı sağlaması yöntemin avantajları arasındadır. [7][8][9][10] Ancak çocuk hastalarda HKA çoğunlukla ebeveynler veya sağlık personeli yardımıyla kullanılmaktadır.…”
Section: Introductionunclassified
“…Despite these limitations many randomized controlled trials have demonstrated that use of Interscalene brachial plexus block with continuous catheter insertion system and disposable infusion pump is associated with better analgesic effect, reduced requirement of opioid analgesics and overall feeling of improvement in patients undergoing shoulder surgeries [7] . Popularity of this technique is increasing with point of care ultrasound (POCUS) using high frequency probes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). With the use of ultrasound imaging excellent gray scale images of brachial plexus and its trunks, cords and divisions can be well demonstrated which consequently greatly improve accuracy with which perineural catheter is placed.…”
Section: Introductionmentioning
confidence: 99%
“…Patient controlled analgesia is another possibility [9] . Many studies have reported a combination of a continuous background infusion and patient controlled analgesia is a better option than either patient controlled analgesia or continuous infusion alone and is associated with superior analgesia, reduced requirement of opioid drugs and faster recovery [10] . We conducted this prospective comparative study of patients undergoing open reduction and internal fixation of fracture of head of humerus under interscalene brachial plexus block and postoperatively received continuous perineural infusion of either normal saline (Group S) or 0.2 % Ropivacaine infusion (Group R).…”
Section: Introductionmentioning
confidence: 99%